Kampanye Penghentian Klitoridektomi dan Peran Strategis HIMPSI - Amriel, Reza Indragiri (Bina Nusantara University, 2010)
If the word ?mutilation? entered in internet search engine, pages appear will be about ?female genital mutilation? (FGM). Association about mutilation and female genital mutilation gives a negative connotation to ?mutilation? term, that is such harmful practical towards women. This connotation affects Indonesia, as according to UNICEF (2005), Indonesia is one of many countries practicing FGM. Besides considering psichological concequences that will harm women, circumcision phenomenon in women unlocks sensitivity in self-judging towards Islam community as the major community in Indonesia. This paper bring up description about FGM and its strategic consideration about psychologic part taken care by Indonesian Psychology Association (HIMPSI) as its future agenda.